Who benefits from quality competition in health care? A theory and a laboratory experiment on the relevance of patient characteristics - Jeannette Brosig-Koch; Burkhard Hehenkamp; Johanna Kokot (University of Hamburg, Hamburg Center for Health Economics (HCHE), 2022)
We study how competition between physicians affects the provision of medical care. In our theoretical model physicians are faced with a heterogeneous patient population, in which patients systematically vary with regard to both, their responsiveness to the provided quality of care and their state of health. We test the behavioral predictions derived from this model in a controlled laboratory experiment. In line with the model, we observe that competition significantly improves patient benefits as long as patients are able to respond to the quality provided. For those patients, who are not able to choose a physician, competition even decreases the patient benefit compared to a situation without competition. This decrease is in contrast to our theoretical prediction implying no change in benefits for passive patients. Deviations from patient-optimal treatment are highest for passive patients in need of a low quantity of medical services. With repetition, both, the positive effects of competition for active patients as well as the negative effects of competition for passive patients become more pronounced. Our results imply that competition can not only improve but also worsen patient outcome and that patients' responsiveness to quality is decisive.
Keywords: I11; D43; C91; 330; physician competition; patient characteristics; heterogeneity in quality responses; fee-for-service; laboratory experiment